(untitled) (World Science, 2023)
Stress reaction in general the meaning of this term includes the entire set of standard, stereotypical, genetic fixed processes that take place at the cellular, tissue and system levels. Research on animals is of great importance in studying the problems of mental pathological conditions. Special attention in such studies, attention is paid to the behavior of animals that are on the border between normality and pathology. After all, understanding that how sick animals behave, on which are affected by stress, weighs a lot to understand how people behave in similar situations. The aim of the work is to investigate the anti-stress effect of pyridoxine and its effect on tryptophan metabolism in the central nervous system under conditions of experimental emotional stress. Pyridoxine, which is a coenzyme of many enzyme systems of tryptophan exchange, when administered under EC conditions, leads to a statistically significant, compared to the control, decrease in the level of tryptophan in all the studied structures of the brain: cortex, stem, cerebellum, and hypothalamus. At the same time, the level of serotonin in all structures reliably increases to control values, and in the cortex it even exceeds them.